The Business Models of mLabs and mHubs : An Evaluation of infoDev's Mobile Innovation Support Pilots - World Bank (Washington, DC, 2014)
In 2010, infoDev, the government of Finland, and Nokia launched the Creating Sustainable Businesses in the Knowledge Economy (CSBKE) program to derive and test new approaches to advancing innovation and entrepreneurship in developing countries. Based on the vast growth of mobile content and access technology, a large part of the program focused on support for innovation in mobile applications and software (or apps ). Through CSBKE, the concept of mobile entrepreneurship enablers was developed, of which two forms were tested: Mobile Application Laboratories (mLabs) and Mobile Social Networking Hubs (mHubs). mLabs are specialized mobile app business incubation and acceleration service providers; mHubs focus on mobile tech community building by convening stakeholder groups at informal gatherings. mLabs were intended to reach a region comprising several countries, whereas mHubs serve only a single city. Underpinning the mLab and mHub models was the conviction that the enhancement of local innovation ecosystemscharacterized by effective partnerships and coordination amongst stakeholderswould improve the enabling environment for mobile entrepreneurship. infoDev also ran a number of global projects (such as innovation competitions) and training sessions, complemented by analytical products, such as qualitative evaluations, a major report on user and app ecosystems in developing countries, and a generic business model for mLabs.